The Institution of Supervision in Polish Local Government in the Light of the Principle of Proportionality - Monika Augustyniak (Bratislava Law Review)
The idea of the proportionality principle is related to the application of appropriately moderate actions of public authorities and minimising their interference in the sphere of individual rights and freedoms. This principle, also known as the principle of commensurability, is essentially addressed to the legislator and to public administration bodies, including supervisory bodies. The purpose of this paper is to present the institution of supervision in Polish local self-governments in the light of the proportionality principle. Establishing the legal basis of this principle and its impact on the application of supervisory measures in the Polish supervisory procedure concerning the activities of local self-government units. This will, in the final assessment, allow conclusions to be drawn with regard to the legal issue considered.